MENINGKATKAN KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) PADA PESERTA DIDIK KELAS VIII SMP NEGERI 33 MAKASSAR - Nur Rahma Khairunnisa; Wa Mahariya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to improve learning outcomes in writing observation report texts using the Problem Based Learning (PBL) model for class VIII students at SMP Negeri 33 Makassar. This type of research is classroom action research with a group learning method, the research design used is group learning to write text reports on observation results using images and audio-visual media. Research procedures include planning, implementation, observation and reflection in the form of a cycle consisting of cycle I and cycle II. The subjects in this research were 25 students in class VIII of SMP Negeri 33 Makassar. The results of the research and analysis of the results based on cycles 1 to cycle 2 were carried out using the Problem Based Learning (PBL) learning model using different media in learning to write observation report texts. The use of the Problem Based Learning (PBL) model with image media in cycle I resulted in an average score in writing report texts resulting from observation reports, namely 53.4. Then, the use of the Problem Based Learning (PBL) model with audio visual media in cycle II resulted in an average score in writing report texts resulting from observation reports, namely 86. In cycle II the ability to write observation report texts using the Problem Based Learning model (PBL) with audio visual media has increased. Based on the results of this research, it can be concluded that learning outcomes have an influence on the use of the Problem Based Learning (PBL) model with audio-visual media on the skills of writing text reports on observation results for class VIII SMP Negeri 33 Makassar.